Analysis of fish spoilage by gas chromatography–mass spectrometry and electronic olfaction bionic system. Issue 6 (25th October 2018) - Lv, Riqin; Huang, Xingyi; Aheto, Joshua Harrington; Mu, Lijun; Tian, Xiaoyu
Abstract: Freshness is an important index of fish quality. The present study deployed an electronic olfaction bionic system based on colorimetric sensor array (CSA) to evaluate the freshness of Larimichthys crocea. Total volatile basic nitrogen (TVB‐N) content and total viable counting (TVC) of samples were also determined by traditional methods. Gas chromatography–mass spectrometry (GC–MS) was applied for the analysis of volatile organic compounds (VOCs). A support vector regression (SVR) model was built to establish the relationship between the signals of CSA and the values of TVB‐N and TVC of samples. The results obtained demonstrated that the CSA showed potential to evaluate the fish freshness of unknown fish samples qualitatively by predicting TVB‐N and TVC. Furthermore, the CSA could be used as nondestructive technique to evaluate fish freshness. Practical applications: Fish is very popular all over the world because of its nutrition and delicious taste. Therefore, it is an important food and occupies a very important position in the daily dietary structure of residents. However, fish is highly perishable after harvesting and postmortem as a consequence of biochemical and microbial breakdown mechanisms. The TVB‐N and TVC are important indexes of fish freshness evaluation. In this study, a novel CSA is proposed for quantification of TVB‐N and TVC during fish spoilage. This method simplified detection steps and shorten the detection time. The results indicated that the method based on CSA provided a feasible way for simple, rapid detection of TVB‐N and TVC in aquatic products. The method can be applied for rapid detection of aquatic products by both government testing departments and food companies.